Analysis of touching sensation based on weights of rectangular object - Mohd Rizon, Mohamed Juhari; Nabilah, H.E; Ali, M.H; Talha, K.S; Farahiyah, N; Wan, K; Hazry, D; Shahriman, A.B; Razlan, Z.M; Ariffin, M.A; Haslina, M (2015)
A wired glove system is developed by designing a low cost dataglove which has the similar function with the conventional dataglove and has been named as GloveMAP. The system involves the finger movements with some of grasping activities to investigate the force exerted on the fingertips during grasping a rectangular object with different weight. Force sensing resistors (FSR) are attached to the thumb, index and middle fingers to obtain the voltage changes from the activities of fingers grasping. The output data from different weight of rectangular object during grasping are analyzed based on statistical approaches. The correlation between weight and force has been determined by comparing the gradient slope between both graphs.